Theoretical and Methodological Approach of Diagnostics of Innovation and Investment Potential of the Enterprise - Polozova, T. V.; Kyslichenko, A. P.; Mokhammed Rabeakh (ХНУРЕ, 2021)
The proposed theoretical and methodological approach to the diagnosis of innovation and investment potential of the enterprise involves a certain sequence of stages, the use of which in practice will provide the necessary information to make effective decision making management.
Keywords: innovation potential; investment potential; diagnostics of innovation and investment potential